Communications, media and the imperial experience: Britain and India in the twentieth century - Kaul, Chandrika (Palgrave Macmillan, 2014)
Presenting a communicational perspective on the British empire in India during the 20th century, the book seeks to examine how, and explain why, British proconsuls, civil servants and even the monarch George V, as well as Indian nationalists, interacted with the media, primarily British and American, and with what consequences.
Description based upon print version of record
Keywords: Electronic books